The secret life of Lincoln Jones - Van Draanen, Wendelin (Alfred A. Knopf, an imprint of Random House Children's Books, 2016)
Lincoln Jones is always working on the latest story he's got going in his notebook. Those stories are his refuge. A place where the hero always prevails and the bad guy goes to jail. Real life is messy and complicated, so Lincoln sticks to fiction and keeps to himself. Which works fine until a nosy girl at his new school starts prying into his private business. She wants to know what he's writing, where he disappears to after school, and why he never talks to anybody.